Men’s perspectives of male hormonal contraception - Lloyd, Alison L.; Waterfield, Jackie (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In recent years there have been great developmental advances in male hormonal contraception (MHC). Despite this, research relating to men’s perspectives of MHC is sparse and is usually based on questionnaires completed as part of clinical trials. This study explored men’s perspectives of MHC, specifically how they were formed and what factors might be influencing them. Methods: This qualitative study used semi-structured interviews with 10 heterosexual men aged between 18 and 44 within the UK. Using a philosophical standpoint of social constructionism, data were analysed employing a modified grounded theory method. Joint analysis and reflexivity were applied to reduce bias and ensure rigour in the analytical process. Results: Four principal higher order themes emerged from the data: Sexual health and trust within a sexual relationship; Choice; Change; and Health. This paper presents the findings from the first two. Participants believed that MHC use would be affected by issues such as individual sexual relationships, sexual health, and trust. Issues relating to efficacy, contraceptive choice, age, knowledge and methods of administration were seen as core issues relating to the decision to take a MHC drug. Conclusions: This study was successful in its aim, finding that overall MHC would be well received by men and that their perspectives were not that different from attitudes towards female hormone contraception. It also identified potential barriers based on the concerns that men have for themselves and for society were an MHC to become available.